Adenosine Triphosphate Neutralizes Pneumolysin-Induced Neutrophil Activation. (23rd May 2020) - Cuypers, Fabian; Klabunde, Björn; Gesell Salazar, Manuela; Surabhi, Surabhi; Skorka, Sebastian B; Burchhardt, Gerhard; Michalik, Stephan; Thiele, Thomas; Rohde, Manfred; Völker, Uwe; Hammerschmidt, Sven; Siemens, Nikolai
Abstract: Background: In tissue infections, adenosine triphosphate (ATP) is released into extracellular space and contributes to purinergic chemotaxis. Neutrophils are important players in bacterial clearance and are recruited to the site of tissue infections. Pneumococcal infections can lead to uncontrolled hyperinflammation of the tissue along with substantial tissue damage through excessive neutrophil activation and uncontrolled granule release. We aimed to investigate the role of ATP in neutrophil response to pneumococcal infections. Methods: Primary human neutrophils were exposed to the pneumococcal strain TIGR4 and its pneumolysin-deficient mutant or directly to different concentrations of recombinant pneumolysin. Neutrophil activation was assessed by measurement of secreted azurophilic granule protein resistin and profiling of the secretome, using mass spectrometry. Results: Pneumococci are potent inducers of neutrophil degranulation. Pneumolysin was identified as a major trigger of neutrophil activation. This process is partially lysis independent and inhibited by ATP. Pneumolysin and ATP interact with each other in the extracellular space leading to reduced neutrophil activation. Proteome analyses of the neutrophil secretome confirmed that ATP inhibits pneumolysin-dependent neutrophil activation. Conclusions: Our findings suggest that despite its cytolytic activity, pneumolysin serves as a potent neutrophil activating factor. Extracellular ATP mitigates pneumolysin-induced neutrophil activation. Abstract : Granule effector proteins of neutrophils play a crucial role in pneumococcal clearance. Uncontrolled neutrophil degranulation can result in tissue pathology. Pneumolysin is a major pneumococcal cytoplasmic trigger of neutrophil degranulation. Extracellular ATP binds pneumolysin and neutralizes excessive pneumolysin-mediated neutrophil activation.